The oldest hominin butchery in European mid-latitudes at the Jaramillo site of Untermassfeld (Thuringia, Germany). Issue 94 (May 2016) - Landeck, Günter; Garcia Garriga, Joan
Abstract: The late Early Pleistocene site of Untermassfeld, dated to the Jaramillo subchron (ca. 1.07 millions of years ago), is well known for its rich Epivillafranchian fauna. It has also recently yielded stone artefacts attesting hominin occupation. Now, we report here, for the first time, evidence of hominin butchery such as cut marks and intentional hammerstone-related bone breakage. This probable subsistence behaviour was detected in a small faunal subsample recovered from levels with Mode 1 stone tools. The butchered faunal assemblage was found during fieldwork and surveying in fluvial riverbanks (Lower Fluviatile Sands) and channel erosion sediments (Upper Fluviatile Sands). The frequent occurrence of butchery traces on bones of large-sized herd animals (i.e., Bison ) may imply a greater need for meat in seasonal habitats characterised by a depletion of nutritive plants in winter. Early access to carcasses, before their consumption by carnivores, provided hominins with sufficient quantities of meat. This access was acquired with a Mode 1 lithic industry, to ensure food procurement and survival at high latitudes in Europe. Stone tools and faunal remains with signs of anthropic intervention recovered at Untermassfeld are evidence of the oldest hominin settlement at continental mid-latitudes (50° N).